VISUALIZATION OF BIOLOGICAL TISSUE IMPEDANCE PARAMETERS - V. I. Bankov (Бюллетень сибирской медицины, 2016)
Objective. Investigation the opportunity for measurement of biological tissue impedance to visualize its parameters.Materials and methods. Studies were undertook on the experimental facility, consists of registrating measuring cell, constructed from flat inductors system, formed in oscillatory circuit, herewith investigated biological tissue is the part of this oscillatory circuit. An excitation of oscillatory circuit fulfilled by means of exciter inductor which forms impulse complex modulated electromagnetic field (ICM EMF). The measurement process and visualizations provided by set of certificated instruments: a digital oscillograph AKTAKOM ADS-2221MV, a digital generator АКТАКОМ AWG-4150 (both with software) and a gauge RLC E7-22. Comparative dynamic studies of fixed volume and weight pig’s blood, adipose tissue, muscular tissue impedance were conducted by contact versus contactless methods. Contactless method in contrast to contact method gives opportunity to obtain the real morphological visualization of biological tissue irrespective of their nature.Results. Comparison of contact and contactless methods of impedance measurement shows that the inductance to capacitance ratio X(L) / X(C) was equal: 17 – for muscular tissue, 4 – for blood, 1 – for adipose tissue. It demonstrates the technical correspondence of both impedance registration methods. If propose the base relevance of X (L) and X (C) parameters for biological tissue impedance so contactless measurement method for sure shows insulating properties of adipose tissue and high conductivity for blood and muscular tissue in fixed volume-weight parameters. Registration of biological tissue impedance complex parameters by contactless method with the help of induced ICM EMF in fixed volume of biological tissue uncovers the most important informative volumes to characterize morphofunctional condition of biological tissue namely X (L) / X (C).Conclusion. Contactless method of biological tissue impedance measurement is more informative and dynamic and able to mirror morphologic features of organ’s tissue, since it does not depend from electric field divergence lines, electrode polarization and their localization, what takes place during contact method of impedance measurement. Contactless method of biological tissue impedance measurement can be applied as the base diagnostic method – dynamic volumogaraphy.